SYSTEM FOR AUTOMATIC CONTROL OF THE ROTATION FREQUENCY OF AN ELECTROMOTOR OF THE CUTTING MECHANISM OF MACHINE FOR PRODUCTION OF SLICE VENEER (Innovation in Woodworking Industry and Engineering design, 2026)
This paper presents the structure and functions of system for automatic control of the ro-tation frequency of an alternating current powerful electromotor of the cutting mechanism of machine for slice veneer production. In the system a microprocessor programmable frequency regulator for the supplying of the controlled electromotor have been inbuilt. There is already the automated system integrated, as a result of which the productivity ofthe veneer slice machine has improved significantly, the specific energy consumption hasreduced and the intellectual pressure of the operator has decreased.